Pengaruh Pemanasan Berulang terhadap Sifat Fisikokimia dan Kandungan Asam Palmitat pada Minyak Goreng - Yunahara Farida; Irene Frederika Siregar (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Determination of physicochemical properties and contents of its palmitic acid of cooking oil have been done. The treatment of physicochemical properties of cooking oil was carried out after heating on temperature 150, 170, 200 and 225°C for 7 days and then it was stored. The result showed that physicochemical properties from the refractive index, specificic gravity, acid values, peroxide values, total carbonil and thiobarbituric acid, are increased but iodine values is decreased by treated on temperature and time stored. The content of palmitic acid from palm oil which determine by gas chromatography decreased on the third days of storing.